2015
DOI: 10.1080/00036846.2015.1093085
|View full text |Cite
|
Sign up to set email alerts
|

Using newspapers for tracking the business cycle: a comparative study for Germany and Switzerland

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Grossarth‐Maticek and Mayr () find that the R‐word index is suitable for detecting turning points in the business cycle in real time. Iselin and Siliverstovs () find that media indicators are helpful for one‐quarter‐ahead forecasts. Partly, they are even better than other indicators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grossarth‐Maticek and Mayr () find that the R‐word index is suitable for detecting turning points in the business cycle in real time. Iselin and Siliverstovs () find that media indicators are helpful for one‐quarter‐ahead forecasts. Partly, they are even better than other indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Second, both studies consider only short‐term horizons. Grossarth‐Maticek and Mayr () focus on the first two lags (1 and 2 quarters), whereas Iselin and Siliverstovs () concentrate only on the one‐step‐ahead forecast. In contrast, we examine different horizons varying between 1 and 12 months ahead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many studies that evaluate the effects of the SOX in the United States have struggled to find appropriate control samples (Leuz & Wysocki, 2016). This study exploits that two neighboring countries, Austria and Switzerland, are comparable with Germany along important dimensions such as institutional characteristics, accounting traditions, and macroeconomic conditions (Daske & Gebhardt, 2006;IMF, 2013;Iselin & Siliverstovs, 2016;Kaufmann et al, 2009;Spamann, 2010) but had no significant enforcement changes during the study's sample period (Brown et al, 2014;Christensen et al, 2013). Thus, publicly listed firms in Austria and Switzerland provide a useful control sample for a difference-in-differences (DiD) analysis.…”
Section: Enforcement Managerial Discretion and The Informativeness Of Accruals 707mentioning
confidence: 99%
“…Our findings are in line with recent research by [53], who found that the use of optimized news-based sentiment values yielded accuracy gains for forecasting US industrial production. For Switzerland and Germany, [54] obtained improvements in accuracy of one-step-ahead GDP forecasts by augmenting benchmark autoregressive models with variations in the recession-word index. Similarly, [55] found that accounting for consumer and business sentiments led to the improved forecast accuracy of consumption in Indonesia.…”
Section: 𝐼𝐶𝐼mentioning
confidence: 99%